Mediators between Yoga Practice and Psychological Well-Being: Mindfulness, Body Awareness, and Satisfaction with Body Image - Tihanyi, Benedek T.; Böőr, Petra; Emanuelsen, Lene; Köteles, Ferenc (European Journal of Mental Health, 2016)
Regular yoga practice was connected to higher levels of psychological well-being in cross-sectional and longitudinal studies. However, the psychological mechanisms of this connection are still unexplained. In the present cross-sectional questionnaire study, hypothesised mediating effects of body awareness, satisfaction with body image, and mindfulness were investigated. 203 healthy adults (183 females, mean age: 36.8 ± 10.03 years) practicing yoga at an advanced level were involved in the study. Participants completed online questionnaires assessing body awareness (BAQ), dissatisfaction with body image (BIQ), mindfulness (MAAS) and well-being (WHO-5). Body awareness, body image dissatisfaction and mindfulness showed significant correlations with the weekly frequency of yoga practice as well as with psychological well-being. Body awareness, body image and mindfulness mediated the connection between yoga practice and well-being. In the regression analysis, body image dissatisfaction and body awareness remained connected to well-being even after controlling for practice frequency, mindfulness, gender and age. According to these results, body awareness, body image satisfaction and mindfulness are mediators of the connection between yoga practice and well-being.